Intraspecific variation of the wood anatomical features in Lagerstroemia speciosa (L.) Pers. - Asim, Mohammad; Gupta, Sangeeta; Jawaid, Mohammad; Nasir, Mohammed; Hakeem, Khalid Rehman (Forestry Department Peninsular Malaysia, 2014)
Lagerstroemia (L.) Pers. genus has 50 species, distributed in Indo- Malayan region, Polynesia, South-East Asia and Australia. L. speciosa is a medium sized deciduous tree cultivated in most parts of India for its beautiful flowers in the garden and as an avenue tree. Beside this, wood of L. speciosa is used in the construction of beams, doors, windows and in other furniture. The objective of this research was to study the wood microstructure, effect of locality on the microstructure and its relationship with vessel diameter, vessel frequency, ray height and ray width. The samples of the L. speciosa were collected from different geographical areas. It was found that that inter-vessel pit, ray-vessel pit, ray height and ray width vary with the locality but vessel diameter did not show significant variations. It was also observed that the vessel diameter, vessel frequency, ray height, ray width, inter-vessel pit and ray vessel pit frequency have insignificant correlation with the site whereas ray width and ray frequency showed direct correlation.